TDSF: Two-phase tamper detection in semi-fragile watermarking using two-level integer wavelet transform - Amrullah, Agit; Ernawan, Ferda; Anis Farihan, Mat Raffei; Liew, Siau-Chuin (Elsevier B.V., 2025)
Image watermarking is one of techniques that can be used to protect and recover from the altered images. Tamper detection in semi-fragile still does not achieve high accuracy for tamper localization, especially in malicious attacks. This study proposes two-phase tamper detection in semi-fragile image watermarking using two-level Integer Wavelet Transform (IWT). The study proposes two-phases of tamper detection to achieve a high level of accuracy in the tamper localization. The initial phase will check four segments to determine the tampered bit or not. A tampered segment is identified if it contains at least one tampered bit. The second phase will be performed if the first phase has no tampered bit. The second phase checked each segment to determine whether it was tampered with or not. This study also used Normalized Hamming Similarity (NHS) to classify malicious and incidental attacks. The proposed scheme performed two-level integer wavelets transform to obtain the LL, LH, HL, and HH sub-bands. The authentication bits of LL are embedded into the LH and HL sub-bands to generate a watermarked image. The LH and HL are compared using XOR bitwise with authentication bit to localize the tamper detection. The experimental results show that the proposed scheme achieved high quality of the recovered images with an average PSNR score of 44.1864 dB, wPSNR score of 46.2218 dB and SSIM score of 0.9945. The proposed method produced high accuracy of tamper detection of about 98.33 % under object manipulation with the tampering rate of about 12.1643 %.